AA-03 Neuronal-surface P-antigen (NSPA), target of anti-ribosomal P autoantibodies, is expressed in proximal tubule epithelial cells (PTEC): potential role in lupus nephritis. (August 2018) - Bravo-Zehnder, Marcela; Gajardo, Patricia; Valenzuela, Daniela; Toledo, Tomás; Jurado, Ángel; Segovia, Fabián; Méndez, Gonzalo; Vio, Carlos; Massardo, Loreto; González, Alfonso
Abstract : Background: Patients with systemic lupus erythematosus (SLE) and anti-ribosomal P (anti-P) antibodies may present lupus psychosis, cognitive impairment and lupus nephritis (LN). Our group provided a molecular mechanism to explain the neuronal alterations in SLE identifying the neuronal-surface P-antigen (NSPA) as an anti-P target involved in the regulation of synaptic glutamatergic transmission (Bravo-Zehnder et al. A and R 2015; Segovia-Miranda et al. A and R 2015). There is evidence suggesting that anti-P and anti-dsDNA antibodies have the potential to perturb the function of renal cells in addition to complement activation. The mechanism of anti-P association with lupus nephritis remains unclear. It is possible that direct anti-P interaction with cell surface components activates intracellular signalling pathways resulting in renal cell damage. As a first approximation to this hypothesis we study whether and where NSPA is expressed in the kidney. Methods: NSPA expression was assessed by RT-PCR, immunoblot and anti-NSPA immunohistochemistry in C57 WT mice, ß-galactosidase (ß-gal) histochemistry staining in transgenic mice bearing a LacZ gene under the promotor of NSPA gene and anti-P staining in the surface of primary cultures of PTEC and the human kidney cell line HK2. NSPA polarized distribution was studied in Madin-Darby canine kidney (MDCK) cells transfected with NSPA-GFP expression plasmid. The pathogenic potential of anti-P antibodies was analyzed by immunizing C57 WT and NSPA KO mice with recombinant P0 ribosomal bearing (P0 wt ) or not the P epitope (P0 tr ) and testing anti-P and anti-dsDNA presence, proteinuria and renal pathology by histochemistry and electron microscopy. Results: NSPA is expressed in PTEC cells and display a mainly apical distribution in vivo and in vitro, including the transfected MDCK cells. Both P0 wt and P0 tr generated high levels of anti-P antibodies and some mice also developed anti-dsDNA antibodies. Mice presented mild proteinuria at 6 months of immunization. C57 WT and NSPA KO mice immunized with either P0 wt or P0 tr also displayed perivenular lymphocytic infiltration, a mild renal pathology change. In addition, NSPA KO mice, even in absence of anti-dsDNA, showed mesangial electron dense-deposits with discrete effacement of foot processes. Conclusions: NSPA is expressed in both PTEC and polarized MDCK epithelial cells with a polarized distribution that precludes direct interaction with circulating anti-P antibodies, which might access to this target only after glomerular filtration. Circulating anti-P can associate with mild kidney damage independently of NSPA expression, at least in non-lupus prone mice. Acknowledgements: CONICYT Basal grant PFB12/2007 and FONDECYT Grant 1160513.